The Development of Biology Teacher Students’ Abilities in Writing Lesson Plan Using the P-D-C-A-E Steps with Providing Feedback - Kamtet, Wanpen (Ratchaphruek Journal, 2023)
This research was a study to develop biology teacher student’s ability in writing the lesson plans with the P-D-C-A-E steps with providing feedback. The purposes of this research were to: (1) Develop biology teacher students’ abilities; and (2) Study biology teacher students’ satisfactions. The target group consisted of 31 third-year biology student teachers at Nakhon Pathom Rajabhat University in the academic year 2022, who were selected through purposive sampling. The research instruments included a training activity on writing the lesson plans with the P-D-C-A-E steps and providing feedback, a feedback recording form, an assessment form for the lesson plan, a questionnaire on the perceived difficulty of writing the lesson plan, and a satisfaction assessment questionnaire. Data were analyzed by mean, standard deviation, and the Wilcoxon Signed-Rank Test. The research findings indicated that biology teacher student demonstrated significantly higher abilities in writing the lesson plans after the intervention compared to before (statistically significant at p < .05). The overall satisfaction on the P-D-C-A-E steps and providing feedback was high (mean = 4.44, S.D. = 0.42).